HIJRAHTAINMENT: COMPOSING PIETY AND PROFANE AS COMMODIFICATION OF RELIGION BY MEDIA - Ratri Rizki Kusumalestari (MediaTor (Jurnal Komunikasi), 2020)
According to the constructionism paradigm in communication and media theory, social reality is constructed by the media based on its ideology. The media construct various realities in the real world into a second reality. One of them is the rise of artists who explore Islam and decide to "emigrate" or “hijrah.” Using the Murray Edelman framing method, this study explores how online media okezone.com, detik.com, and tribunnews.com frame the hijrah phenomenon of  Indonesian artists in entertainment packages and bring up the term hijrahtainment. The results of this study show that the media construct two frames, namely the ideal millennial frame and the piety and profane frame. The categorisation from the three online media offers religion commodification in the frame of piety, mixing with profanity like entertainment.